PELAKSANAAN DAN TINDAK LANJUT LAPORAN EVALUASI BADAN PEMERIKSA KEUANGAN ATAS HASIL PEMERIKSAAN AKUNTAN PUBLIK PADA BADAN USAHA MILIK NEGARA - cahyo anggoro; Dewi Kania Sugiharti (Universitas Widya Gama Malang, 2018)
Law Number 19 of 2003 regulates that the implementation of state financial management and accountability audits in State Owned Enterprises is conducted by Audit Board and Public Accountants. Law Number 15 of 2004 and Law Number 15 of 2006 regulates if the state financial audit is conducted by a public accountant in accordance with the provisions of other laws, the report of this audit result shall be submitted to Audit Board. Audit Board will evaluate the report and then submit the evaluation result and the public accountant's audit report to the representative body. This research will describe the implementation of Audit Board evaluation on the result of public accountant audit of State Owned Enterprises financial report and follow up on the implementation of the evalauation conducted by related parties.The research used normative legal research method. The researcher will conduct an inventory of positive laws related to researc,. Data collection includes data collection at Audit Board, House of Representative, and the Ministry of Finance.Based on the results of research known that Audit Board is not effective in conducting evaluation of the results of public accountant audit of the financial statements of State Owned Enterprises. Audit Board only conducts an evaluation of several reports. Follow-up on the report is used by the Ministry of Finance to provide administrative sanctions for public accountants who are considered not in accordance with the standards in conducting the audit. The House of Representatives uses the evaluation report as one of the materials in carrying out supervision over the management of State Owned Enterprises. In the future, there should be a clear regulation to regulate the evaluation so that each party knows and understands the rights and obligations, including the sanctions.Kata kunci: Badan Pemeriksa Keuangan; Badan Usaha Milik Negara; Evaluasi Hasil Pemeriksaan Akuntan Publik; Tindak Lanjut Pemeriksaan